Structure-property relationship of reconstructed collagen from food waste - Cheam, Nicole Mein Ji (Nanyang Technological University, 2024)
Food security and sustainability have become increasingly critical concerns due to the growing population and limited land resources. Ensuring the sustainable production of nutritious food has become a major challenge, yet there is a problem of food waste. Aquaculture food waste, including fish and frog skin, contains valuable collagen, which can be valorized rather than discarded. This collagen is rich in essential amino acids, making it a potential alternative source of protein. Collagen has been widely used in tissue engineering applications, along with its derivative, gelatin, which is also often used in food applications as thickeners and stabilizers. Although gelatin is frequently used in food applications due to its excellent gelling capabilities, it is often only used as an additive rather than the primary component of food products. Its thermo-reversible gelation properties limit its versatility in food applications. To address this gap, this study explores a microbial transglutaminase (mTgase)-gelatin system for producing gels with a wide range of mechanical and organoleptic properties capable of withstanding boiling. The gelatin used in this study was extracted from the discarded skin of Atlantic salmon (Salmo salar), Barramundi (Lates calcarifer), and American bullfrog (Rana catesbeiana). These gelatins were characterized to understand their intrinsic gelling properties. Subsequently, food-grade mTgase was employed to crosslink the gelatin, introducing thermal stability to the gels. The study delved into various parameters such as mTgase concentration, gelatin concentration, and crosslinking temperature to manipulate the gel structures and establish the structure-property relationship of mTgase-crosslinked gelatin gels. An essential focus was to establish relationships between the functional groups of imino acid influencing physical crosslinking, and glutamine affecting chemical crosslinking with the storage modulus of the gels. From the results obtained, phase diagrams were constructed to show the sol-gel transition of gelatin based on these functional groups. This understanding is valuable for manipulating the structure and properties of gelatin gels based on their amino acid content regardless of the gelatin source. Overall, the mTgase-gelatin system holds promising potential as a platform for developing food products aimed at addressing the challenges of food security and sustainability.